General anesthesia plus ilioinguinal nerve block versus spinal anesthesia for ambulatory inguinal herniorrhapy - Lucía Vizcaíno-Martínez; Manuel Ángel Gómez-Ríos; Beatriz López-Calviño (Saudi Journal of Anaesthesia, 2014)
Objective: The aim was to evaluate general anesthesia (GA) plus ilioinguinal nerve block (IIB) versus spinal anesthesia (SA) in patients scheduled for ambulatory inguinal hernia repair regarding pain management, anesthesia recovery and reducing potential complications. Materials and Methods: A double-blind, prospective, randomized, controlled study in patients American Society of Anesthesiologists I-III randomized into two groups: GA plus IIB group, induction of anesthesia with propofol, maintenance with sevoflurane, airway management with laryngeal mask allowing spontaneous ventilation and ultrasound-guided IIB; SA group, patients who underwent spinal block with 2% mepivacaine. The study variables were pain intensity, assessed by visual analog scale, analgesic requirements until hospital discharge, time to ambulation and discharge, postoperative complications-related to both techniques and satisfaction experienced. Results: Thirty-two patients were enrolled; 16 patients in each group. The differences regarding pain were statistically significant at 2 h of admission (P < 0.001) and at discharge (P < 0.001) in favor of the GA plus ilioinguinal block group. In addition in this group, analgesic requirements were lower than SA group (P < 0.001), with times of ambulation and discharge significantly shorter. The SA group had a higher tendency to develop complications and less satisfaction. Conclusion: General anesthesia plus IIB is better than SA regarding postoperative analgesia, time to mobilization and discharge, side-effect profile and satisfaction experienced by the patients.